Association between arsenic and different-sized dissolved organic matter in the groundwater of black-foot disease area, Taiwan. (September 2016) - Chen, Ting-Chien; Hseu, Zeng-Yei; Jean, Jiin-Shuh; Chou, Mon-Lin
Abstract: The formation of an arsenic (As)-dissolved organic matter (DOM) complex is important in driving the release of arsenic in groundwater. This study collected groundwater samples from a 20 m deep well throughout 2014 and separated each into three subsamples by ultrafiltration: high molecular weight-DOM (HDOM, 0.45 μm–10 kDa), medium molecular weight-DOM (MDOM, 10–1 kDa), and low molecular weight-DOM (LDOM, <1 kDa) solutions. The fractional DOM was measured with a three-dimensional excitation-emission matrix (EEM) via fluorescence spectroscopy. A fluorescence quenching method was used to calculate the apparent stability constant ( K s ) between arsenic and the fractional DOM. Based on the EEM records, three fluorescence indicators were further calculated to characterize the DOM sources, including the fluorescence index (FI), the biological index (BI), and the humification index (HI). The experimental results indicated that arsenic in the groundwater was mainly partitioned into the MDOM and LDOM fractions. All fractional DOMs contained humic acid-like substances and were considered as microbial sources. LDOM had the highest humification degree and aromaticity, followed by MDOM and HDOM. The As and DOM association could be formed by a Fe-bridge, which was demonstrated by the K s values and fourier transform infrared (FTIR) spectra of the DOM. The formation of AsFe-DOM complex was only significant in the MDOM and LDOM. Highlights: The complexation of As and DOM was demonstrated by using the fluorescence technique. Arsenic was mainly partitioned into the small sized-dissolved organic matters. All fractional DOMs were considered as microbial sources. The formation of AsFe-DOM complex was significant in the smaller sized-DOMs.